Predictive prognostic modelling of refrigeration systems - Zhou, Qin Tian (Nanyang Technological University, 2024)
A refrigeration system refers to a mechanical process of controlling and regulating the thermodynamic cycle, resulting in the cooling of between two points. It is widely used in substantial buildings comprising multiple storages such as shopping malls, hotels, hospitals and office towers. Predictive and prognostic modelling represents statistical techniques aimed at predicting future risks or events. Predictive modelling endeavors to anticipate future behaviors based on historical data while prognostic analytics looks for causes and effects. Applying the predictive Machine Learning (ML) methodologies and refrigeration system fundamentals to the database of refrigeration system, this project aims to build a predictive and prognostic model to detect and forecast system faults